2017
DOI: 10.1007/s11682-017-9782-z
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal interaction between cognitive control network and affective network in patients with end-stage renal disease

Abstract: End-stage renal disease (ESRD) is a common complicated disorder that is generally associated with an altered central nervous system and cognitive impairment. Neuroimaging studies have recorded aberrant brain circuits in patients with ESRD that were closely associated with abnormal clinical manifestations. However, whether the altered interaction was within and/or between these circuits is largely unclear. We investigated brain topological organization and/or module interaction by employing resting-state functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 52 publications
9
16
0
Order By: Relevance
“…One focus of this study was the SN due to its role on the brain end of the renal-brain axis. Our current findings were generally consistent with earlier reports, for example, recent studies have reported gray matter loss (Zhang et al, 2013), disrupted white matter microstructure (Mu et al, 2018a), elevated cerebral blood flow (CBF) (Jiang et al, 2016), and dysconnectivity (Mu et al, 2018b) in the SN in patients. The SN is engaged in identifying and responding to salient stimuli, as well as recruiting relevant largescale functional networks for advanced cognition (Chand and Dhamala, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…One focus of this study was the SN due to its role on the brain end of the renal-brain axis. Our current findings were generally consistent with earlier reports, for example, recent studies have reported gray matter loss (Zhang et al, 2013), disrupted white matter microstructure (Mu et al, 2018a), elevated cerebral blood flow (CBF) (Jiang et al, 2016), and dysconnectivity (Mu et al, 2018b) in the SN in patients. The SN is engaged in identifying and responding to salient stimuli, as well as recruiting relevant largescale functional networks for advanced cognition (Chand and Dhamala, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, ESRD patients reported cognitive decline, mainly in working memory, attention, processing speed, accompanied by depression, which was consistent with previous research (Dong et al, 2016). Recent rs-fMRI research also found that abnormal interaction between the SN and affective network, which laid the neural foundation of the abnormal interaction between depressive mood and cognitive control deficits in ESRD patients (Li et al, 2018;Mu et al, 2018b). And the FC between the right anterior insula and the right supramarginal gyrus significantly positively correlated with MoCA, which meant the decreased FC may predict the cognitive impairment in ESRD patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Higher global efficiency seems to indicate effective integrity and rapid information propagation between and across remote brain regions [54,55]. For our earlier studies, decreased global efficiency has previously been reported in functional brain networks [56]. Here, the increased global efficiency in the structural network may suggest of self-regulation of the brain.…”
Section: Discussionsupporting
confidence: 50%
“…Higher global efficiency seems to indicate effective integrity and rapid information propagation between and across remote brain regions [54,55]. For our earlier studies, decreased global efficiency has previously been reported in functional brain networks [56]. Here, increased global efficiency in the structural network may suggest self-regulation of the brain.…”
Section: Discussionsupporting
confidence: 50%